How do physicochemical properties influence the toxicity of silver nanoparticles on freshwater decomposers of plant litter in streams? - Batista, Daniela (2017)
AgNP physicochemical properties may affect AgNP toxicity, but their effects on plant litter decomposition and the species driving this key ecosystem process in freshwaters have been poorly investigated. We assessed the impacts of AgNPs with different size and surface coating (100 nm PVP (polyvinylpyrrolidone)-dispersant, 5060 nm and 35 nm uncoated) on freshwater decomposers of leaf litter by exposing leaf associated microbial assemblages to increasing concentrations of AgNPs (up to 200 mg L-1) and of AgNO3 (up to 25 mg L-1). We further conducted a feeding preference experiment with a common invertebrate shredder, Limnephilus sp., which was allowed to feed on microbially-colonized leaves previously exposed to AgNPs and AgNO3. Leaf decomposition and microbial activity and diversity were inhibited when exposed to increased concentrations of 100 nm AgNPs (>= 25 mg L-1), while microbial activity was stimulated by exposure to 35 nm AgNPs (100 mg L-1). Invertebrate shredders preferred leaves exposed to 35 nm AgNPs (25 mg L-1) and avoided leaves exposed to AgNO3 (>= 2 mg L-1). Results from the characterization of AgNPs by dynamic light scattering revealed that AgNps with PVP-dispersant were more stable than the uncoated AgNPs. Our results highlight the importance of considering the physicochemical properties of NPs when assessing their toxicity to litter decomposers in freshwaters.